2021
DOI: 10.1002/jor.24985
|View full text |Cite
|
Sign up to set email alerts
|

One‐year outcomes following physical therapist‐led intervention for chronic hip‐related groin pain: Ancillary analysis of a pilot multicenter randomized clinical trial

Abstract: Evidence related to physical therapist-led intervention for patients with chronic hiprelated groin pain (HRGP) is limited. The purpose was to assess sustainability of treatment effects for people with HRGP undergoing two physical therapist-led interventions. We completed an ancillary analysis of a pilot multicenter, randomized clinical trial. Forty-six patients with chronic HRGP, 15-40 years, were enrolled. Patients were randomized to participate in 10 sessions over 12 weeks of either movement pattern training… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…38 Improving hip flexor flexibility has also been proposed as a target, although limited research suggests that addressing hip flexor flexibility in isolation does not lead to carryover in functional tasks. 58 Training specific movements with improved pelvic motor control may be of benefit, 23,59,60 however generalized strength and flexibility interventions may produce similarly beneficial patient-reported outcomes 60 and more research is needed in this area. While there are several potential targets, it is not established if pelvic tilt can be changed because of a specific or generalized rehabilitation plan, or if specifically tracking the change in pelvic tilt might be a useful prognostic factor for a successful outcome.…”
Section: Discussionmentioning
confidence: 99%
“…38 Improving hip flexor flexibility has also been proposed as a target, although limited research suggests that addressing hip flexor flexibility in isolation does not lead to carryover in functional tasks. 58 Training specific movements with improved pelvic motor control may be of benefit, 23,59,60 however generalized strength and flexibility interventions may produce similarly beneficial patient-reported outcomes 60 and more research is needed in this area. While there are several potential targets, it is not established if pelvic tilt can be changed because of a specific or generalized rehabilitation plan, or if specifically tracking the change in pelvic tilt might be a useful prognostic factor for a successful outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Standard postoperative care +in-patient physiotherapy for gait aid +written education material +requested to not undertake formal rehabilitation programme. 80 Wright et al 72 (n=18) showed a large but non-significant between-group difference on HOS-Sport at 6-week follow-up in favour of hip exercises performed at home versus manual therapy and supervised physiotherapy for FAI syndrome (mean difference: 21.1 points, 95% CI −9.1 to 51.3, Hedges g=1.27) (very low quality of evidence).…”
Section: Prescribed Post-operative Physiotherapy Vs Advicementioning
confidence: 99%
“…22 However, 12-month follow-up suggests that within-group improvements are retained, indicating a potential long-term effect of nonoperative treatment outcome. 80 Due to the heterogeneity of physiotherapy interventions between these studies, it seems difficult to recommend a specific non-operative treatment approach (eg, movement pattern training vs hip strengthening) beyond exercise-based treatment. 12 The mechanisms of improvements following exercise-based treatment are yet to be elucidated, but may be related to improvements in hip muscle strength 14 and altered hip joint kinematics (ie, reduced hip adduction angle during single leg squatting) 111 potentially reflecting better load-bearing capacity of the hip joint.…”
Section: Diagnosis and Clinical Informationmentioning
confidence: 99%